Evaluating psychiatry residency program website content. Issue 3 (3rd July 2021) - Bernstein, Simone A.; Bhat, Nisha R.; Harmon, Tara G.; Nguyen, Bambi; Gu, Alex; Marks, Lauren A.; Gold, Jessica A.
Abstract: Objective: When psychiatry residency applicants apply for residency, many use program websites to learn information about the program. In this study, the content of websites was evaluated for comprehensiveness. Method: Using the Accreditation Council for Graduate Medical Education (ACGME) list of residency programs for 2020, 255 residency training websites were identified and evaluated. The categories analyzed included program overview, application information and recruitment, and educational opportunities. The program websites were all evaluated via descriptive statistics. Results: Analysis of the content on the websites found that a majority included a general overview of the program (99.2%), but fewer included a rotation schedule (43.9%), the number of trainee positions (42.0%), a diversity and inclusion statement (39.2%), and the employers of past residents (21.2%). Conclusion: Psychiatry residency website have room for improvement. Due to COVID-19, applicants will obtain a large amount of information via websites. This only makes it more critical that websites are regularly updated and provide comprehensive information to make informed decisions.